Protest Participation and Social Media Engagement of College Students: The case of July Uprising in Bangladesh - Mondal, Md Sanaul Haque (PARTECIPAZIONE E CONFLITTO, 2026)
In July 2024, students from several universities in Bangladesh turned out to the streets to reform job quotas in government services. The government used excessive force to stop protest, leading to widespread violence in the country. Soon after the government's brutal actions, many people, including college students, took to the streets to demand justice for barbaric acts. This study examined Bangladeshi college students' protest participation and willingness to participate in future social movements. A survey was conducted with 125 college students after the July 2024 protest. Descriptive and inferential statistics were computed. All statistical analyses were done using SPSS (version 26). Most respondents were male (72%), with an average age of 18.31 years. Only 12.8% had personal income, and 71.2% were in Grade 12. About 66% were from a Bengali medium background, and 61.6% were science students. The study found that 77.6% participated in protests physically, while 91.2% were active on social media. Additionally, 90.4% expressed willingness to participate in future social movements. Regression analysis showed that age, sex, medium of instruction, faculties, and state repression significantly influence participation in the protest physically. On the other hand, kinship sentiment and state repression demonstrated a correlation with online protest participation. The willingness to participate in future social movements was found to be associated with social media engagement and the perceived well-being of the nation. These findings are very useful for researchers and policymakers to challenge the existing notion that youths are reluctant or have limited interest in social issues, civic engagement, and participation.